Customer Understanding of the Profit-Sharing Ratio at Muamalat Bank - Fitria Ayu Lestari Niu; Karlina Aprilianingrum Bawenti; Syarifuddin Syarifuddin (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2022)
This study aims to determine the customer understanding of the profit-sharing ratio at Muamalat Bank Branch Manado using a qualitative method. The data in this study were obtained through triangulation techniques consisting of interviews, observations, and documentation. The data analysis method used includes the stages of data reduction, data presentation, and concluding. The result showed that, generally, the customer understanding of the profit-sharing ratio of savings products at Bank Muamalat is still inadequate. Customers do not understand clearly and in detail savings products (names and types of the savings product). It caused customers not to get an explanation and product knowledge from the bank at the beginning of the account opening. In explaining his understanding of profit-sharing, the customer depends on his educational background and profession. Customer understanding can also be seen from the selected savings products where the main informant has prime savings while the regular informant chooses everyday savings. The implications for knowledge are sozialication role from the bank, educational and occupational backgrounds as factors that affect the level of customer understanding. For the bank to provide feedback as material for the improvement of the quality of banking services and products based on Islamic principles and competitive for its share